Online environmental activism in Turkey: The case study of “The Right to Water” - Şen, A. Fulya; Şen, Y. Furkan (Routledge, 2016)
This article intends to contribute to research of environmental media activism in two ways: First, by discussing ways to frame research on this topic conceptually and historically. Second, by considering the specific strategies and experiences of environmental activist groups concerning activist medias and participatory actions. We will discuss what can be done when using Internet platforms. “The Right to Water” website has been selected as a case study, which is essentially a democratic platform against capitalist ecology policies. In this study, we examined Internet usage by environmentalist activist groups, by collecting and analyzing data on the usage and results of web-based activism, and discuss the impact of online activism within civil society. © 2016, © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Environmental movements; internet; online activism; public sphere; “The Right to Water”